Analisis Komparatif Daya Dukung Tanah & Penurunan Pondasi Menggunakan Metode Analitis Dan Metode Elemen Hingga (Studi Kasus : Borehole 1 Proyek Apartment Mega Techno City Di Kota Batam) - Mauthonic, Valerianus Kevin; Ginting, Jody Martin (Jurnal Ilmiah Rekayasa Sipil, 2023)
Batam City is a city with high attractiveness for tourists, both local and foreign tourists. In an effort to support and accommodate tourists visiting the city of Batam, the construction of hotels and apartments has been intensively carried out. Due to limited land, the high rise building model is one of the most effective building models to build. To guarantee high rise building performance, it is necessary to plan well in design from a structural point of view. In this case foundation as one of the elements of the structure is also an important part, so it needs to be planned well too. The bearingXcapacity of theXfoundation and the settlement in the foundation areXtwo important things that need to beXconsidered in foundation planning. In this study, an analysis of the bearing capacity of the foundation using the Meyerhof method and the finite elementXmethod (Plaxis 2D) and foundation settlement analysis using the elastic reduction method and the finite elementXmethod (Plaxis 2D) was carried out on the Mega Techno City Apartment construction project in Batam. The results of this analysis are in the form of bearing capacity based on the Meyerhof method is 3.330,8 kN and 3.351,6 kN based on the finite element method, as for the settlement, 53,1 mm is obtained for the elastic settlement method and 9,64 mm for the finite element method, the settlement still meets the SNI 8640 – 2017 standard. Based on these external differences, it can be used as a reference in conservative design.